eHealth Game Jams provide prototypes for health care - Arpola, Tiina (Finnish Journal of eHealth and eWelfare, 2018)
Digitalisation and Information and Communication Technologies (ICT) for health and wellbeing are crucial today for providing high - quality care. Gamified solutions can be used in health care to promote health of the customers or to train health care professionals. Games for Health Finland network activates co-creation workshops, Game Jams, for creating prototypes for more efficient health care. These events bring together people with different backgrounds with a spark of innovation and to get a break from their normal routines and working environment. During the eHealth2018 conference a short Game Jam that lasted only 18 hours was organized, with 20 jammers from across the Finland. As a result we got 5 prototypes that was introduced at the end of the conference to the conference audience.